Evolution of the Neopsylla hongyangensis Mitogenome: Insights Into the Mitogenomic Evolution of the Orders Siphonaptera and the Phthiraptera - Xiaoxia Lin; Ju Pu; Wenge Dong (Ecology and Evolution)
ABSTRACT The evidence that parasitic animals exhibit elevated mitogenomic evolution rates is inconsistent and limited to Arthropoda. Neopsylla hongyangensis Li, Bai et Chen, 1986 (Siphonaptera: Ctenophthalmidae) feeds on the host's blood and is an important medical insect with plague transmission. In this study, we sequenced the N. hongyangensis mitogenome and explored the mitogenomic evolution of Siphonaptera and Phthiraptera, which both belong to the Insecta on warm‐blooded animals. The mitogenomes of Siphonaptera are closed‐circular double‐stranded DNA molecules and exhibit highly conserved structural features. In contrast, the mitogenomes of most Phthiraptera species exhibit extensive fragmentation and comprise multiple minichromosomes. We performed a comparative analysis of nucleotide composition, Ka/Ks ratios, and codon usage patterns in Siphonaptera and Phthiraptera mitogenomes. Compared to Phthiraptera with low locomotory capacity, Siphonaptera with high locomotory capacity have higher AT content, slower evolution, and greater influence from natural selection (i.e., micro‐habitat). The mitogenomic evolution of Siphonaptera and Phthiraptera was influenced by locomotory capacity and life history. Phylogenetic analysis based on 13 PCGs showed that Ceratophyllidae, Leptopsyllidae, and Ctenophthalmidae were paraphyletic, and Vermipsyllidae, Hystrichopsyllidae, Pulicidae, and Pygiopsyllidae were monophyletic. This study provides new insights into the phylogenetic relationships and mitogenomic evolution of Siphonaptera.